Students Perception towards Traditional Game in Improving Students' Motivation in English Language Learning - Arsita, Dita; Sain, Yuliyanah; Nasrullah, Rahmat (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores students’ perceptions of using the traditional game Lengko-lengko to enhance motivation in English learning. A descriptive qualitative method was employed with 15 seventh-grade students at SMP Negeri 20 Kendari as participants, selected through purposive sampling. Data were collected through semi-structured interviews and documentation, then analyzed using Miles and Huberman’s interactive model. The findings reveal that Lengko-lengko fosters three aspects of intrinsic motivation: curiosity, enjoyment, and sense of achievement. Students showed eagerness to explore new vocabulary, experienced greater enjoyment through interactive and collaborative activities, and developed pride and confidence from their achievements during the game. These aspects created a continuous motivational cycle that supported active participation, cultural appreciation, and positive attitudes toward English learning. The study suggests that integrating traditional games into teaching strategies not only enriches students’ language learning experiences but also preserves cultural values.